2013
DOI: 10.1021/ja410124v
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Prebiotic Formation of a β-Ribofuranoside That Self-Assembles with a Complementary Heterocycle

Abstract: The RNA World hypothesis is central to many current theories regarding the origin and early evolution of life. However, the formation of RNA by plausible prebiotic reactions remains problematic. Formidable challenges include glycosidic bond formation between ribose and the canonical nucleobases, as well as the inability of nucleosides to mutually select their pairing partners from a complex mixture of other molecules prior to polymerization. Here we report a one-pot model prebiotic reaction between a pyrimidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
101
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 38 publications
7
101
0
1
Order By: Relevance
“…Chemical evolution could have been driven by non-enzymatic templatedirected replication and functional selection by geophysical cycles (e.g., day-night, wet-dry, hot-cold, freeze-thaw). Although such a process has not yet been demonstrated experimentally, alternative monomers and reactions are being found that support the possibility that proto-RNA and proto-polypeptides could have formed in simple dryingheating reactions Chen et al 2014). Additionally, theoretical studies have indicated the potential for functional evolution to take place within a pool of random informational polymers if there is a repeating cycle in which one phase promotes sequence-independent polymer replication, with an alternating phase of limited polymer hydrolysis and monomer recycling, all in an environment of low diffusivity (e.g., a viscous solvent) (Walker et al 2012).…”
Section: Testing the Poole Hypothesismentioning
confidence: 99%
“…Chemical evolution could have been driven by non-enzymatic templatedirected replication and functional selection by geophysical cycles (e.g., day-night, wet-dry, hot-cold, freeze-thaw). Although such a process has not yet been demonstrated experimentally, alternative monomers and reactions are being found that support the possibility that proto-RNA and proto-polypeptides could have formed in simple dryingheating reactions Chen et al 2014). Additionally, theoretical studies have indicated the potential for functional evolution to take place within a pool of random informational polymers if there is a repeating cycle in which one phase promotes sequence-independent polymer replication, with an alternating phase of limited polymer hydrolysis and monomer recycling, all in an environment of low diffusivity (e.g., a viscous solvent) (Walker et al 2012).…”
Section: Testing the Poole Hypothesismentioning
confidence: 99%
“…This ordering through assembly could then provide a catalyst for polymerization of protonucleic acid polymers, by aligning their functional groups. Additionally, these molecules are attractive protonucleic acid nucleobase candidates, as triaminopyrimidine forms glycosidic linkages with ribose to produce nucleosides in water, and barbituric acid, cyanuric acid, and melamine have been found in model prebiotic reactions [142,143].…”
Section: Selectionmentioning
confidence: 99%
“…295 The system was based on two monomers derived from nucleic acid base pairing mimics using a basic triaminopyrimidine and an acidic cyanuric acid derivative as recognition units. [295][296][297] The copolymers are most stable when the pH of the medium equals the pK a of the monomers but disassemble in response to pH changes. 295 Shifts of the apparent pKa value is a well-known phenomenon for polymeric weak acids, self-assembled fatty acids and amphiphilic block copolymers, [298][299][300][301][302][303][304][305] and has been used by many research labs in order to fine-tune the pH-triggered self-assembly of linear 306,307 and aromatic peptide amphiphiles.…”
mentioning
confidence: 99%